Currículo em ciências contábeis: estratégias de aprendizagem para os tempos contemporâneos - Rodrigues, Luciana Gavazzi Barragan (2021)
Considering the scene during the XXI Century, the discussion about the future of the Accounting Science professional has become usual upon Nacional and International Congresses. As a result of these debates, it was built some innovative Curricular Projects to cater to the formation of the said professionals. The possibilities of these curricula fulfill their goals depend on the change upon each of their curricular components, from the definition of their intention (formation goal) to the remaining of the evaluation process, going through the change of the teacher’s and the student’s attitudes and the implementation of participative methodologies. On this research, it is detached one of these curricular components – Learning Techniques - integrated to the Project, in order to investigate which changes it demands and how to implement them to contribute to the formation of the Accounting Science professional. Our searching issue: What strategies2 can be applied in a graduation Accounting Science course aiming the development of competent professionals and citizens to the contemporaneous society? It’s about a theorical cleat, in a qualitatively approach, through where it’s intended to comprehend and deepen, in an specialized literature, the thought and the meaning that the authors show about the Learning Strategies integrated to a curriculum and the meaning that they give to this curricular component, likewise to the basic clues to the implementation. The obtained results point towards a new comprehension of the Strategies and meaningful suggestions to develop innovative curricula in Accounting Science